Pengaruh Pemanfaatan Teknologi Informasi Dan Kompetensi Sumber Daya Manusia Terhadap Kinerja Karyawan Pada Kelurahan Makassar Jakarta - Sonny Fransisco Siboro; Ahmad Taufik (Prisani Cendekia, 2022)
This study aims to determine and analyze the influence of Information Technology and HR Competencies on employee performance at the Makassar City Office, East Jakarta. The purpose of this study was to determine the extent to which Information Technology and HR Competencies significantly affect employee performance at the Makassar Village Office, East Jakarta. In this study, the samples taken were 35 people. The analytical method used in this study is multiple linear regression analysis, namely Y = 27,086 + 0.0751 + 0.0042. Information Technology has a positive and insignificant effect on employee performance, HR competence has a positive and insignificant effect on employee performance. Simultaneously, Information Technology and HR Competence have a positive and insignificant effect on employee performance.